Analisis Metode Montessori dalam Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas Rendah SD/MI - Nura Azkia; Nur Rohman (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Reading is the highest function that comes from the human brain. Reading as a basic foundation in academic ability. Therefore the introduction of the letter 'reading' as a first step to teach children / students in knowing, understanding, and inferring the meaning of reading. The purpose of this study provides a new concept of the montessori method in reading the beginning of children / students in Indonesian language lessons in low grades. This library research will explain validly and objectively about the related analysis. The research relies on sources from various established bibliographies such as scientific articles, theses and books. Then integrated into the substance of research or content analysis. The results of this study are: (1) providing a new pattern in stimulating understanding in reading the beginning of children/ students, (2) providing concepts in strengthening the absorption reading the beginning of children/students, (3) meeting the needs in the period sensitive and intellectual structure in learning to read the beginning of children/ students, (4) Development of new materials on the montessori method in concrete Indonesian language learning to improve the ability to read the beginning of children/students.